2012
DOI: 10.2495/wm120181
|View full text |Cite
|
Sign up to set email alerts
|

Influential factors on the oil agglomeration process for coal recovery from different grade coals

Abstract: Large amounts of waste fine coals are produced, which are difficult to be treated because of high ash content and inorganic sulfuric compounds. In order to make efficient use of waste fine coal, a retrieval technique is necessary for the recovery of coal combustible content from fine waste coals. Nowadays, the floatation process can be used, but it is impractical for developing countries due to high costs, then the oil agglomeration process can deal with these problems. In this study, we investigated the affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This was undertaken to determine the degree of weathering of the coal surfaces. Coal oxidation is denoted by the intensity of the oxygenated functional groups such as the hydroxyl (O-H) and carbonyl (C=O) (Wang et al, 2012). A distinct and intense peak of O-H groups is present for sample 2, suggesting that the coal is highly weathered.…”
Section: Ftir Spectra For the Five Coal Samples W/o Emulsion And Kero...mentioning
confidence: 99%
“…This was undertaken to determine the degree of weathering of the coal surfaces. Coal oxidation is denoted by the intensity of the oxygenated functional groups such as the hydroxyl (O-H) and carbonyl (C=O) (Wang et al, 2012). A distinct and intense peak of O-H groups is present for sample 2, suggesting that the coal is highly weathered.…”
Section: Ftir Spectra For the Five Coal Samples W/o Emulsion And Kero...mentioning
confidence: 99%
“…In the formula, agglom and feed denotes recovered agglomeration and coal samples, respectively, and wt gives the weight unit (g). In equations ( 6)- (10), SS and PS are the contents of sulfate sulfur and pyrite sulphur, respectively, and CM is 100 -(ash content) [8,9]. R (%) = 100 × wt agglom (g) / wt feed (g) ( 5) SSR (%) = 100 × (1 -SS agglom (%) × wt agglom (g)) / (SS feed (%)× wt feed (g) ( 6) PSR (%) = 100 × (1 -PS agglom (%) × wt agglom (g)) / (PS feed (%)× wt feed (g) ( 7) CMR (%) = 100 × CM agglom (wt.%) ×wt agglom (g) / (CM feed (wt.%) × wt feed (g)) ( 8) AR (%) = 100 -100×Ash agglom (wt.%) ×wt agglom (g) / (Ash feed (wt.%) × wt feed (g)) ( 9)…”
Section: Experiments Of Oil Agglomeration Adjusted Ph Of Solutionmentioning
confidence: 99%
“…In recent days influencing factors of the oil agglomeration process were investigated by experiments using different grade coal and it was concluded that aromatic and aliphatic functional groups of carbonaceous content had an important function. However, the oil agglomeration process has not been put to practical use because the coal cleaning efficiency is low and usage of recovered carbonaceous content is not discussed [7,8]. We need to accumulate the data for commercial viability of oil agglomeration in the future.…”
Section: Introductionmentioning
confidence: 99%